The Surface Revolutionary Approach to Surface Area and Volume of a Sphere - Baraily, Khagendra; Yadav, Annada Kumar (The Journal of DMC, 2026)
The surface area and volume of sphere can easily be explained as a revolution of a sector of circle in space and can be derived from the area of the circle. This study depicts the amount of changes in the derivation of surface area and volume of solid from the area of plane geometric figures that are obtained after revolution. It begins with the derivation of the surface area and volume of cylinder, cone and then extending the idea up to the solid sphere as a revolution of a right sector of a circle in space. This is an alternative and revolution method of geometric figures (i.e. the method of surface revolution) for the derivation of surface area and volume of a solid. This method of computation facilitates to find the area of rectangular region on the surface of sphere and the volume of the pyramid having the rectangular base on the surface of the sphere and vertex at the center of the sphere. This article has presented completely new idea and different pattern of computation.